From work to word - Frohnapfel, Doris (Bergen Kunsthogscholen Bergen, 2002)
Scarce publication exploring the relationship between theory and art and image and text. Includes contributions from Common Culture Group, Dieter Daniels, Mark Durden, Verena Kuni, N55, Jorg Sasse, Duane Michals, Adib Fricke, Arne Skaug Olsen, Yvonne Spielmann, Sharon Kivland, Tanya Ury. 111 pages, illustrations. Light crease to front cover corner, no inscriptions, tight binding with no reading creases. All books dispatched same or next working day in robust packaging. Bookseller Inventory # 000462